2007
DOI: 10.11646/zootaxa.1634.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A new species of Macrosiphoniella and redescription of Coloradoa heinzei (Hemiptera: Sternorrhyncha: Aphididae) as a new record in Iran

Abstract: Apterous and alate viviparous females of Macrosiphoniella kermanensis sp. nov. living on Artemisia sieberi (Asteraceae) are described from Iran. Also, Coloradoa heinzei (Borner) from Artemisia aucheri (Asteraceae), as a new record in Iran, is redescribed. A key to the apterous viviparous females of Macrosiphoniella del Guercio species living on Artemisia in Iran is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Some dwarf apterae (small body) were collected on Mentha piperita in Jiroft (the weather is sweltering in summer -it is one of the hottest places in Iran -but temperatures are moderate in winter), Kerman province which identification of them was problematic (Ilharco, 1987), but using morphometric methods it revealed that they belong to A. affinis (unpublished data). (Alikhani et al, 2010;Hodjat, 1993;Mehrparvar et al, 2007;Mehrparvar et al, 2021Mehrparvar et al, , 2022Mehrparvar et al, 2008;Mokhtari et al, 2012;Momeni Shahraki et al, 2019;Mousapour, 2016;Rezwani, 1987Rezwani, , 2010Rezwani & Parvizi, 1990;Rezwani et al, 1994;Samii, 1992) Aphis ballotae (Hodjat, 1993;Momeni Shahraki et al, 2019;Rezwani, 1987Rezwani, , 2010Rezwani et al, 1994;Samii, 1992;Sedighi, 2019) Aphis craccivora Koch, 1854…”
Section: -Aphis Affinis Del Guercio 1911 (Aphididae: Aphidinae: Aphid...mentioning
confidence: 99%
“…Some dwarf apterae (small body) were collected on Mentha piperita in Jiroft (the weather is sweltering in summer -it is one of the hottest places in Iran -but temperatures are moderate in winter), Kerman province which identification of them was problematic (Ilharco, 1987), but using morphometric methods it revealed that they belong to A. affinis (unpublished data). (Alikhani et al, 2010;Hodjat, 1993;Mehrparvar et al, 2007;Mehrparvar et al, 2021Mehrparvar et al, , 2022Mehrparvar et al, 2008;Mokhtari et al, 2012;Momeni Shahraki et al, 2019;Mousapour, 2016;Rezwani, 1987Rezwani, , 2010Rezwani & Parvizi, 1990;Rezwani et al, 1994;Samii, 1992) Aphis ballotae (Hodjat, 1993;Momeni Shahraki et al, 2019;Rezwani, 1987Rezwani, , 2010Rezwani et al, 1994;Samii, 1992;Sedighi, 2019) Aphis craccivora Koch, 1854…”
Section: -Aphis Affinis Del Guercio 1911 (Aphididae: Aphidinae: Aphid...mentioning
confidence: 99%
“…The numbers of aphid species described in the world are increasing day by day. This is also true for Iranian aphid fauna so that the numbers of aphid species recorded in Iran are more than 470 species (Hodjat, 2005;Mehrparvar & Rezwani, 2007;Özdemir & Barjadze, 2015;Goodarzifar et al, 2016;Mehrparvar, 2016Mehrparvar, , 2017Barjadze et al, 2017;Kanturski & Barjadze, 2018) which could be increased up to 550 species by further investigations.…”
Section: Introductionmentioning
confidence: 95%
“…Macrosiphoniella species living on Artemisia (Asteraceae) in Iran (updated from the keys of Blackman & Eastop (2016) and Mehrparvar & Rezwani (2007)).…”
Section: Key To the Apterous Viviparous Females Ofmentioning
confidence: 99%
“…So far, more than 260 aphid species are reported on Artemisia worldwide, which is by far the largest aphid fauna of any plant genus (Blackman & Eastop 2006;Holman 2009). Up to now, 32 aphid species are reported from Iran associated with Artemisia (Table 1) (Hodjat 1993;Mehrparvar & Rezwani 2007;Rezwani 2010). The genus Macrosiphoniella is originated in the Palaearctic with about 120 species in the world (Heie 1995;Remaudière & Remaudière 1997;Blackman & Eastop 2016), which at least half of them feed on Artemisia, so being the most abundant genus of aphids on Artemisia (Blackman & Eastop 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation